2017
DOI: 10.1111/avj.12547
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between transitional lumbosacral vertebrae and eight lumbar vertebrae in a breeding colony of Labrador Retrievers and Labrador Crosses

Abstract: When performing screening radiographs for TLSV, assessment for 8LV and fusion of Ca1 to S3 should be included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This study did however not include any of the breeds evaluated in our study. Based on the variable interbreed prevalence, a genetic predisposition has been suggested, with heritability estimates for German Shepherd dogs stated between 0.2 and 0.5 . Heritability of transitional vertebrae has not been investigated in small brachycephalic breeds, but can be considered likely in Pugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study did however not include any of the breeds evaluated in our study. Based on the variable interbreed prevalence, a genetic predisposition has been suggested, with heritability estimates for German Shepherd dogs stated between 0.2 and 0.5 . Heritability of transitional vertebrae has not been investigated in small brachycephalic breeds, but can be considered likely in Pugs.…”
Section: Discussionmentioning
confidence: 99%
“…While the cause and pathogenesis of these malformations remain unknown, most studies support multifactorial etiologies . A recent study has identified a mutation in the gene DVL2 linked with thoracic and caudal vertebral column malformations in English Bulldogs, French Bulldogs, and Boston Terriers but not in Pugs .…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, the anatomical variations and morphologic abnormalities along the spine, including the transitional vertebrae, have been investigated more often than in other species, due to the possibility of using imaging methods and techniques and the well-known predisposition of this species to these modifications. In dogs, the presence of a supernumerary vertebra (L8) is often reported and usually has no clinical importance ( Moeser and Wade 2017 ). Our observations showed that, in general, the L8 is shorter than the last lumbar vertebra when the lumbar region counts 7 vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported an increased probability in the occurrence of the transitional lumbosacral vertebra in the offspring of Labradors when both parents had either eight lumbar vertebrae, a fusion or a reduction in the space between the S3 and Ca1 vertebrae (Moeser & Wade, 2017), and these characteristics were likely to be influenced by major gene effects.…”
Section: Discussionmentioning
confidence: 99%